Efficacy of anti-koi herpesvirus DNA vaccine in carp Cyprinus carpio fry by immersion method and hyperosmotic infiltration. Issue 1 (1st June 2022) - Nuryati, Sri; Soraya, Siti; Alimuddin,
Abstract: Indonesian carp production has decreased due to mass mortality caused by herpesvirus koi infection. Safe prevention techniques can be applied en masse and are relatively inexpensive are needed. This study aimed to examine the effect of immunization using anti-koi herpesvirus (KHV) DNA vaccine at a dose of 1.3 × 108 cfu.mL -1 through immersion with different lengths of time after hyperosmotic infiltration for 2 minutes. There were six groups with three replications: vaccination with 60 minutes immersion (A), 90 minutes (B), 120 minutes (C), non-vaccinated fish but infected with KHV (positive control), non-vaccinated fish and not infected with KHV (negative control), control fishes soaked with whole bacteria (control bacteria without DNA vaccine). The results showed that vaccination for 60 minutes gave the highest relative survival (93.55%). Thus, vaccination by immersion and hyperosmotic infiltration effectively improves the survival and relative survival of fish, and this method can be an alternative in the early control of KHV infection in common carp and koi.